Imaging X-ray Polarimetry Explorer: prelaunch - Weisskopf Martin C.; Soffitta Paolo; Baldini Luca; Ramsey Brian D.; O'Dell Stephen L.; Romani Roger W.; Matt Giorgio; Deininger William D.; Baumgartner Wayne H.; Bellazzini Ronaldo; Costa Enrico; Kolodziejczak Jeffery J.; et al. (Society of Photo-optical Instrumentation Engineers, 2025)
Launched on 2021 December 9, the Imaging X-ray Polarimetry Explorer (IXPE) is a NASA Small Explorer Mission in collaboration with the Italian Space Agency (ASI). The mission will open a new window of investigation-imaging x-ray polarimetry. The observatory features three identical telescopes, each consisting of a mirror module assembly with a polarization-sensitive imaging x-ray detector at the focus. A coilable boom, deployed on orbit, provides the necessary 4-m focal length. The observatory utilizes a three-axis-stabilized spacecraft, which provides services such as power, attitude determination and control, commanding, and telemetry to the ground. During its 2-year baseline mission, IXPE will conduct precise polarimetry for samples of multiple categories of x-ray sources, with follow-on observations of selected targets.